2013
DOI: 10.1007/s13191-013-0313-3
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Study to Identify a Ceramic Polishing Protocol Effecting Smoothness Superior to Glazed Surface

Abstract: Polishing is taken up as an alternative to reglazing after adjustments of glazed ceramic prosthesis. An in vitro study was carried out to evaluate three different ceramic polishing systems and their combinations to identify a method that would achieve surface smoothness superior to the glazed surface. 77 glazed feldspathic porcelain disc surfaces, of diameter 12.5 mm and thickness 2 mm were constituted into seven groups of 11 specimen surfaces each. The glazed surfaces in the first group served as control (C).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…In laboratorial tests, Manjuran and Sreelal41 stated that the combination of polishing system and polishing paste (Shofu Inc.) produced smoother surfaces than the feldspathic ceramics (Vintage Halo, Shofu Inc.). Sarac et al24 described that the use of both a polishing system (Shofu Inc.) and the polishing paste (Ultra II, Shofu Inc.) together generated surfaces as smooth as the ones of the feldspathic ceramic glaze (Vitadur Alpha, VITA).…”
Section: Discussionmentioning
confidence: 99%
“…In laboratorial tests, Manjuran and Sreelal41 stated that the combination of polishing system and polishing paste (Shofu Inc.) produced smoother surfaces than the feldspathic ceramics (Vintage Halo, Shofu Inc.). Sarac et al24 described that the use of both a polishing system (Shofu Inc.) and the polishing paste (Ultra II, Shofu Inc.) together generated surfaces as smooth as the ones of the feldspathic ceramic glaze (Vitadur Alpha, VITA).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors found that the initial smoothness of the glazed surface of ceramic to be superior to the polished surface [16,17] and some authors considered that the polished surface could equal the glazed surfaces. The results of this study concluded that it depends on the type of the ceramic.…”
Section: Ra Parametermentioning
confidence: 99%
“…Ceramic corrosion can affect the roughness of the materials, which can affect the survival rate of the prosthetic restoration [14,15]. Ceramics can be clasified by their microstructure (type of crystalline phase and glass composition), processing technique powder/liquid,pressed, or machined), and clinical application [16]. Furthermore, polishing and glazing are also applied to finalize surface texture of the ceramic material, reduce roughness and enhance light transmission influencing the optical properties.…”
mentioning
confidence: 99%
“…After grinding, manufacturers usually recommend a polishing protocol, which should be executed to achieve a smooth and shining surface (5); and/or a glazing procedure on the surface again to promote a smooth and shining surface (8); and/or a heat treatment/annealing, that consists to subject the zirconia to a specific heat treatment, with temperatures around 1000 ºC for 15 min, aiming for the complete reversion of m to t phase (9).…”
Section: Introductionmentioning
confidence: 99%